Enhancement of Industrial Energy Efficiency and Sustainability - Trianni, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Industrial energy efficiency has been recognized as a major contributor, in the broader set of industrial resources, to improved sustainability and circular economy. Nevertheless, the uptake of energy efficiency measures and practices is still quite low, due to the existence of several barriers. Research has broadly discussed them, together with their drivers. More recently, many researchers have highlighted the existence of several benefits, beyond mere energy savings, stemming from the adoption of such measures, for several stakeholders involved in the value chain of energy efficiency solutions. Nevertheless, a deep understanding of the relationships between the use of the energy resource and other resources in industry, together with the most important factors for the uptake of such measures-also in light of the implications on the industrial operations-is still lacking. However, such understanding could further stimulate the adoption of solutions for improved industrial energy efficiency and sustainability.